Analisis Strategi Pengembangan Sumber Daya Manusia terhadap Kompetensi Dosen Politeknik Negeri Kupang - Batilmurik, Ridolof W; Sahetapy, Stela; Noach, Robert M; Samadara, Pieter D (Jurnal Ilmiah Aset, 2018)
Development strategy of human resources quality of Kupang State Polytechnic can be done to create competent PNK Lecturer in professional, pedagogic, personality and social aspect. The facts show that 119 lecturers have been certified but have not shown competence in their field of expertise, especially on pedagogic and professional aspects. Is the serdos obtained is due to the full right of the lecturer or indeed the lecturer has shown his competence through a number of test instruments conducted through self-description and assessment of the four aspects of the competence. This research entitled analysis of HR development strategy to lecturer competence. The purpose of this study is to find out how education and training are in PNK Kupang and to find out whether partially or simultaneously education and training affect the competence of lecturers. This research is explorative with assoiatif approach (cause- effect). The sample is 54 respondents from 119 lecturers who have been certified using Slovin 10% technique. Data analysis using descriptive and inferential stattistik; niai average respondents’ answers, test instruments of validity and reliabiliats, classical assumptions and multiple regression, and hypothesis test F arithmetic and Thitung. The result of the analysis shows that education and training strategy is able to give positive and significant influence.